Comparison of two methods of mathematical modeling in hydrodynamic sealing gap - Krutil, Jaroslav; Fojtášek, Kamil; Dvořák, Lukáš (EDP Sciences, 2015)
The aim of work is to compare two possible methods of mathematical modeling of hydrodynamic instabilities. This comparison is performed by monitoring the formation and evolution of Taylor vortices in hydrodynamic sealing gap. Sealing gaps are a part of the hydraulic machines with the impeller, such as turbines and pumps, and they have an effect on the volumetric efficiency of these devices. This work presents two examples of sealing gaps. These examples are closed sealing gap and modified sealing gap with expansion chamber. On these two examples are applied procedures of solution contained in CFD software (ANSYS Fluent 14.5). In ANSYS Fluent is two possible basic approaches of solution this task: the moving wall method and the sliding mesh method. The result of work is monitoring the impact of the expansion chamber on the formation of hydrodynamic instabilities in the sealing gap. Another result is comparison of two used methods of mathematical modeling, which shows that both methods can be used for similar tasks.

The aim of work is to compare two possible methods of mathematical modeling of hydrodynamic instabilities. This comparison is performed by monitoring the formation and evolution of Taylor vortices in hydrodynamic sealing gap. Sealing gaps are a part of the hydraulic machines with the impeller, such as turbines and pumps, and they have an effect on the volumetric efficiency of these devices. This work presents two examples of sealing gaps. These examples are closed sealing gap and modified sealing gap with expansion chamber. On these two examples are applied procedures of solution contained in CFD software (ANSYS Fluent 14.5). In ANSYS Fluent is two possible basic approaches of solution this task: the moving wall method and the sliding mesh method. The result of work is monitoring the impact of the expansion chamber on the formation of hydrodynamic instabilities in the sealing gap. Another result is comparison of two used methods of mathematical modeling, which shows that both methods can be used for similar tasks.
Comparison of two methods of mathematical modeling in hydrodynamic sealing gap
Keywords: Mathematical modeling; CFD; sealing gap; flow.; Mathematical modeling; CFD; sealing gap; flow.